Between Text, Technology and Context: Contemporary Ijtihād in the Interpretation of Islamic Legal Sources in the Digital Age - Arip Purkon; Moh. Ali Wafa; Abu Tamrin; Mohd Hafiz Jamaludin (Universitas Islam Sultan Agung, 2026)
Purpose - The rapid development of digital civilisation has fundamentally transformed the methods by which Muslims access, produce, and interpret sources of Islamic law. Concurrently, this transformation necessitates a methodological renewal in contemporary independent juristic reasoning (ijtihād). This article aims to explore a model of Islamic legal interpretation that reconciles the methodological legacy of the Islamic legal theory (uṣūlī) tradition with interpretive practices in the digital age. The study emphasises the integration of meticulous textual analysis, an awareness of contemporary social contexts, and the ethical and responsible application of technology.Methodology/approach - The study employs a qualitative approach characterised by a normative-critical design. The analysis draws upon Islamic legal texts, the literature on Islamic legal theory (uṣūl al-fiqh), and scholarly research on digital religion and technology. Moreover, the analytical framework integrates textual, historical, social, and technological dimensions within the context of the objectives of Islamic law (maqāṣid al-sharīʿah), thereby facilitating a more comprehensive understanding. Building upon this foundation, the study proposes a novel integrative framework that systematically synthesises uṣūl al-fiqh, digital epistemology, and maqāṣid-based ethics.Findings - The findings indicate that classical uṣūl al-fiqh methodologies remain adaptive when reinterpreted through a maqāṣid-oriented and context-sensitive approach. In this regard, digital technology functions not merely as a tool; rather, it also acts as an epistemic agent that shapes contemporary legal reasoning and authority. The article further demonstrates that digital technology holds considerable potential to expand access and enhance efficiency in the interpretation of Islamic law. Nevertheless, its use must be guided by sound methodological principles and scholarly ethics. An integrative interpretive model grounded in text, technology, and context enables Islamic law to remain relevant, authoritative, and oriented towards public welfare (maṣlaḥah) amid ongoing social dynamics and technological developments. The scholarly contribution of this study lies in proposing a conceptual model of digital ijtihād that not only enriches contemporary Islamic legal theory but also provides a foundation for future interdisciplinary research on law, technology, and society.Conclusion - This research advocates for the advancement of a more interdisciplinary ijtihād methodology through the integration of digital literacy, technology ethics, and the framework of maqāṣid al-sharīʿah. This approach aims to enhance Islamic legal interpretation's capacity to address the challenges posed by digital society in a more comprehensive manner.